Anisakis simplex (sensu lato) and Hysterothylacium cornutum (Nematoda: Ascaridoidea) in adult Atlantic bluefin tuna (Thunnus thynnus) caught in Norway - Miguel Bao; Arne Levsen; Lucilla Giulietti; Martin Wiech; Keno Ferter; Egil Karlsbakk; Paolo Cipriani (Food and Waterborne Parasitology)
The Atlantic bluefin tuna Thunnus thynnus is one of the largest and most valuable fish species in the Atlantic Ocean. Its meat is highly appreciated worldwide, particularly in Japan, where it is commonly consumed raw as sushi or sashimi. Here, we investigated the occurrence and species composition of parasitic nematodes in the viscera of adult Atlantic bluefin tuna caught off western Norway. The zoonotic nematodes Anisakis simplex (sensu stricto) and Anisakis pegreffii are reported for the first time in wild large adult specimens. Findings suggest that both anisakids appear unable to penetrate the stomach wall of large tuna. Instead, they remain attached and are associated with pathologies, including crater-like ulcers and tumours, sometimes filled with cyst-like decomposition products. A few anisakid larvae were, however, found encapsulated on the intestine and caeca, suggesting that they may have penetrated the thinner walls of the digestive tract there. These results highlight the need for further research on tuna's muscle to rule out any food safety concerns. Additionally, the raphidascaridid nematode Hysterothylacium cornutum and a single 4th-stage larva of H. aduncum, were identified in the tuna stomachs. Partial LSU rDNA, mtDNA cox2 and ITS rDNA sequences of H. cornutum are reported for the first time. These sequences may aid resolving the taxonomy of the genus Hysterothylacium and unravelling the parasite's life cycle in future studies.